The Stereological Analysis and Spatial Distribution of Neurons in the Human Subthalamic Nucleus - Bokulić, Ema; Medenica, Tila; Knezović, Vinka; Štajduhar, Andrija; Almahariq, Fadi; Baković, Marija; Judaš, Miloš; Sedmak, Goran (Frontiers in Neuroanatomy, 2021)
The subthalamic nucleus (STN) is a small, ovoid structure, and an important site of deep brain stimulation for the treatment of Parkinson’s disease. Although the STN is a clinically important structure, there are many unresolved issues with regard to it. These issues are especially related to the anatomical subdivision, neuronal phenotype, neuronal composition, and spatial distribution. In this study, we have examined the expression pattern of 8 neuronal markers (nNOS, NeuN, PV, CB, CR, FOXP2, NKX2.1 and PAX6) in the adult human STN. All of the examined markers, except CB, were present in the STN. In order to determine the neuronal density, we have performed stereological analysis on Nissl-stained and immunohistochemical slides of positive markers. The stereology data were also used in order to develop a three-dimensional map of spatial distribution of neurons within the STN. The nNOS population exhibited the largest neuronal density. The estimated total number of nNOS STN neurons is 281,308 ± 38,967 (±13.85%). The STN neuronal subpopulations can be divided into two groups: one with a neuronal density of approximately 3,300 neurons/mm3 and the other with a neuronal density of approximately 2,200 neurons/mm3. The largest density of STN neurons was observed along the ventromedial border of the STN and the density gradually decreased towards the dorsolateral border. In this study, we have demonstrated the presence of 7 neuronal markers in the STN, three of which were not previously described in the human STN. The human STN is a collection of diverse, intermixed neuronal subpopulations, and our data, as far as the cytoarchitectonics is concerned, did not support the tripartite STN subdivision.